Undifferentiated pleomorphic sarcoma of the prostate in a young man. Issue 4 (17th June 2020) - Iwahashi, Yuya; Matsumura, Nagahide; Kusumoto, Hiroki; Ozaki, Takashi; Higuchi, Masatoshi; Kohjimoto, Yasuo; Hara, Isao
Abstract : Introduction: Prostate sarcoma is an extremely rare disease with a poor prognosis. Undifferentiated pleomorphic sarcoma has never been described in the prostate. Case presentation: A 27‐year‐old man complained of frequent urination and dysuria for several years. Various examinations were suggestive of prostate sarcoma. The pathological diagnosis was confirmed as prostate sarcoma via ultrasound‐guided transrectal needle biopsy. Because the location of the tumor in the prostate was confirmed by magnetic resonance imaging, we performed robot‐assisted radical prostatectomy. The final pathological diagnosis was undifferentiated pleomorphic sarcoma. Local recurrence occurred at the front of the rectum 2 months after surgery. Although chemotherapy and radiotherapy were initially effective, he died 18 months after surgery. Conclusion: Undifferentiated pleomorphic sarcoma of the prostate is believed to have a poor prognosis. When selecting the surgical procedure, functionality should be considered for individual cases with complete resection.